The Transformation from Fear into Hope in Rise of the Guardians - Kezia Gloria Indah Setiawati (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
Fear and hope are common topics in children's animation film. Famous children’s fantasy characters usually represent the children who overcome their fear and turn it to hope to help the children overcome their fear. Rise of the Guardians is one of the films that rises these topics. This paper aims to prove that Santa Claus, Tooth Fairy, Easter Bunny, Sandman, and Jack Frost in Rise of the guardians really experienced the fear of being forgotten. Then, the paper will show how the guardians as the representation try to overcome the fear by freezing, avoiding the source of fear, and facing the fear. And after that, how they try to transform that fear into hope by gaining a positive mind and finding a new goal. Symbolism theory combines with fear and hope theories are used to analyse these statements. Keywords: Fear, transformation, hope, symbolism in literature, children’s fantasy characters